Principles and modern applications of mass transfer operations - Benitez, Jaime, 1948- (Wiley, 2009)
"The Second Edition of the acclaimed Principles and Modern Applications of Mass Transfer Operations continues to provide a thorough, accessible text that gives students the support and the tools they need to quickly move from theory to application. This latest edition has been thoroughly revised and updated with new discussions of such developing topics as membrane separations, ion exchange, multistage batch distillation, and chromatography and other adsorptive processes. Moreover, the Second Edition now covers mass transfer phenomena in biological systems, making the text appropriate for students in biochemical engineering as well as chemical engineering." "Ideal for a first course in mass transfer operations, this text has proven to be invaluable to students in chemical and environmental engineering as well as researchers and university faculty."--BOOK JACKET.